DNA metabarcoding on roadkill stomach contents reveals the breadth of species present in bobcat diets - Kim A. Hughes; Carol S. Henger; Jason E. Hawley; Evon R. Hekkala; Jason Munshi-South; Tracy A. G. Rittenhouse (PLoS ONE, 2026)
Trophic dynamics can be altered in complex ways as a result of urbanization. Understanding predator diets in these contexts may not only provide insight into these changes, but also in sources of mortality for vulnerable prey species like the New England cottontail ( Sylvilagus transitionalis ). However, studying the diets of mammalian predators such as bobcats ( Lynx rufus ) can be challenging because of their elusive behavior. DNA metabarcoding of stomach contents from roadkill is a method which provides a new opportunity to study predator diets when mortality events occur. We used this technique to examine variation in bobcat diet across a range of urbanized environments in Connecticut, USA, as well as determine whether bobcats consume the declining New England cottontail. DNA metabarcoding identified between two and five species in the majority of bobcat stomachs. Cottontail ( Sylvilagus spp. ) and eastern gray squirrel ( Sciurus carolinensis ) were each found in over 80% of samples, and most remaining taxa were other small mammals. Nearly a third of the bobcats had consumed white-tailed deer ( Odocoileus virginianus ). Stomach contents containing cottontail remains were sequenced at an additional species-specific marker, but no samples containing the New England cottontail were identified. Bobcats in Connecticut consumed a wide variety of natural prey species including a relatively high proportion of semi-aquatic mammals, and we found no evidence of domestic dog or cat consumption. DNA metabarcoding of stomach contents is an effective approach for opportunistically examining predator diet, and our use of this tool may provide a more complete picture of bobcat diet where other techniques have failed to do so.